Handbook of non-invasive drug delivery systems science and technology - Kulkarni, Vitthal S. (William Andrew ; Elsevier Science [distributor], 2009)
With the improvements in formulation science and certain transdermal delivery technologies, the non-invasive mode of drug delivery is now ready to compete with traditional methods of oral and injectible routes of drug delivery. The Handbook of Non-Invasive Drug Delivery Systems encompasses the broad field of non-invasive drug delivery systems that include drug delivery via topical, transdermal-passive, transdermal-active (device- aided enhanced penetration), trans-mucosal membrane, trans-ocular membrane as well as delivery via alveolar membrane from inhaled medication. Patient compliance has been found to be much higher when administrated by non-invasive routes and therefore they are considered to be a preferred mode of drug delivery. The book includes both science and technological aspects of new drug delivery systems. Its unique focus is that it is on new drug delivery systems that are considered to be "non-invasive". Other unique features include a chapter on Regulatory Aspects of non-invasive systems and one on FDA guidance for topical nano-drug delivery. Two chapters covering market trends and perspectives, as well as providing guidance to those marketing such systems are also included.
Keywords: Drug delivery systems.; Transdermal medication.; Oral medication.; elektronické knihy; electronic books